Hybrid Perovskite Solar Cells: 1D Organic–Inorganic Hybrid Perovskite Micro/Nanocrystals: Fabrication, Assembly, and Optoelectronic Applications (Small Methods 7/2018). Issue 7 (12th July 2018) - Xu, Xiuzhen; Zhang, Xiujuan; Deng, Wei; Jie, Jiansheng; Zhang, Xiaohong
Abstract : One‐dimensional organic–inorganic hybrid perovskite micro/nanocrystals (1D PMCs) possess properties that are superior to those of their film counterparts. In article number1700340, Xiujuan Zhang, Xiaohong Zhang, and co‐workers review the fabrication, assembly, and optoelectronic applications of 1D PMCs. In particular, the methods for large‐area aligned/patterned assembly of 1D PMCs are addressed. This provides a guide for the fabrication of integrated devices based on 1D PMCs.